'I Feel Like I Identify as a University Student, I Just Don't Identify with My University' - how First-Year Students Developed their Identities during the COVID-19 Pandemic - Hodgkin, Kieran; Packer, Rhiannon (International Journal of Educational and Life Transitions, 2023)
This study explored, in detail, the development of student identity as students transition to university, during the global COVID-19 pandemic. The study explored the journeys of four first year students from two United Kingdom (UK), Higher Education (HE) institutions and compared their expectations of the transition to HE to their experiences during their first six months of study. The study was underpinned by the principles of case study research with four ‘cases’ across two institutions. This study adopted a narrative approach, utilising paired interviews to explore student identity in relation to social integration and academic belonging. The data analysis was conducted using principles from Lincoln et al.’s (1994) audit trail. Three key themes emerged from the paired interviews: ‘academic belonging’, ‘informal learning conversations’ and ‘intrinsic motivation to study.’ In conclusion, this small-scale, qualitative study has identified that first-year students can develop a sense of ‘academic belonging’ via an online learning environment. Nevertheless, the participants did report experiences of low motivation and isolation, which hindered the development of a student identity. While the longer-term impact on students is uncertain, this study may also serve as a documentation of the experiences of students during the pandemic.
Keywords: university transition; higher education; student identity; first-year undergraduate; paired interviews